Reading buddy: the Indonesian gen Z and millennials bookstagram’s virtual communication practice - Nabilla Anasty Fahzaria; Alexandria Cempaka Harum; Izni Nur Indrawati Maulani; Ferra Martian (Jurnal Studi Komunikasi, 2025)
Abstract Reading activities have shifted to social media platforms. Despite Indonesia having a low reading habit worldwide, it is expanding rapidly among millennial and Gen Z bookstagrammers. This study explores the meaning of ‘reading buddy’, motivations for engaging in virtual ‘reading buddy’ activities, emotional intimacy, habits and continuity of virtual communication with reading buddy partners. Using a cyberphenomenology approach, this study involved in-depth, semi-structured interviews with ten (10) Indonesian millennials and Z generation bookstagrammers by applying Barry Wellman's Networked Individualism Theory. This study's cyberphenomenology data analysis technique refers to the coding colour analysis procedure (CCAP). The study results show that a reading buddy is interpreted as a friend who reads books together, a sharing friend, and community outreach activities. It is known that the shift in social interaction from groups to individuals has opened up opportunities for virtual community bookstagrammers on Instagram to create interests that are appropriate for personal networks. In the reading buddy activities carried out, this is believed to enrich the reading experience while improving communication and literacy skills. Instagram is essential in positively impacting interpersonal relationships, personal development, and individual knowledge, especially among the younger generation who like to read books.